Pharmacoinformatic Based Screening Of Phytocompound Epigallocatechin Gallate To Identify As A Potential Bcl-2 Inhibitor - Balasundari A. (International Journal of Bioinformatics and Computational Biology, 2023)
Objectives: The B-cell lymphoma-2 (Bcl-2) is a protein that is particularly though to be involved in preventing apoptosis. Bcl-2 family members also essential for cancer survival, and its over expression has been linked to tumor genesis, development and resistance to anticancer treatments. The Bcl-2 family of members that inhibit apoptosis is a promising target for the creation of anticancer drugs. Methods: The study was based on computational approach using different phytocompounds for evaluating their potential against Bcl-2 protein. The compound namely epigallocatachin gallate and their similar compounds derived from Pubchem and three known inhibitor of Bcl-2 was selected. Molecular docking was conducted systematically using Pyrex and Biovia to determine the binding affinities between bioactive compounds. The pharmacological characteristics and toxicity of the compounds, analyzed by using Swiss ADME and ADMETlab 2.0. Results: The docking results revealed that some phytocompounds were the best inhibitor of Bcl2 protein, especially (2R,3R)-2-(3,4,5-trihydroxyphenyl) chroman-3-yl 3,4,5-trihydroxybenzoate. Perfectly binds inside the pocket of target protein like standard drug. The pharmacological studies also revealed that non toxicity and carcinogenicity. Conclusion: This computational study finding might help develop potential drug to combat standard drugs. The findings could aid in the creation of affordable, all-natural cancer treatments.
Keywords: Bcell lymphoma 2; Epigallocatechin gallate; Venetoclax; phytocompounds